Development of gas turbine spray test rig for biofuel - N. N., Raupeeh; M. N. M., Jaafar; M. A. A., Arizal; Mohamad Shaiful Ashrul, Ishak (Praise Worthy Prize S.r.l., 2011)
Link to publisher's homepage at http://www.praiseworthyprize.com/